COLLABORATIVE PLANNING TO FACILITATE INTERDISCIPLINARY GERIATRIC CLINICAL APPROACHES - Reed, P.S. (Innov Aging, 2017)
This presentation will provide an overview of the collaborative planning process used to engage multiple health disciplines and community members in developing and launching a new community-based comprehensive geriatric specialty clinic. It will outline results of the key elements of the process, such as the national environmental scan of clinical geriatric models, the regional needs assessments, the collaborative committee structure and disciplinary engagement strategies. It will conclude with an overview of the final clinic model that was implemented.